2013
DOI: 10.1007/s00535-013-0861-7
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant methylation of microRNA-34b/c is a predictive marker of metachronous gastric cancer risk

Abstract: BackgroundMetachronous gastric cancer (GC) can develop after endoscopic resection of GC and cannot be predicted based on clinical signature. Aberrant DNA methylation in noncancerous gastric mucosa is strongly implicated in gastric carcinogenesis and could be a useful biomarker of GC risk. We evaluated the clinical utility of DNA methylation as a biomarker of metachronous GC risk.MethodWe carried out scheduled follow-up endoscopy in 129 patients after curative endoscopic resection of GC. Biopsy specimens were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 36 publications
(41 reference statements)
2
47
3
Order By: Relevance
“…The multivariate analysis showed that atrophic type or intestinal metaplasia was the strong independent risk for DNA methylation after H. pylori eradication. Although DNA hypermethylation might be a risk of gastric cancer regardless of H. pylori infection status [6,[19][20][21], in our study, the most important factor of DNA hypermethylation was magnifying NBI and histologic features. This indicates that the methylation change is closely linked to the magnifying NBI and histologic features within the focal points.…”
Section: Discussioncontrasting
confidence: 50%
“…The multivariate analysis showed that atrophic type or intestinal metaplasia was the strong independent risk for DNA methylation after H. pylori eradication. Although DNA hypermethylation might be a risk of gastric cancer regardless of H. pylori infection status [6,[19][20][21], in our study, the most important factor of DNA hypermethylation was magnifying NBI and histologic features. This indicates that the methylation change is closely linked to the magnifying NBI and histologic features within the focal points.…”
Section: Discussioncontrasting
confidence: 50%
“…Other biomarkers for predicting metachronous cancer development have been reported. Several reports have indicated that assessment of the epigenetic field defect using DNA methylation levels could be used as a predictive marker for metachronous gastric cancer after endoscopic resection . However, this method is not yet practical because of the difficulty of analysis and high cost.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the occurrence of malignant cancer induced by aberrant methylation-caused gene disability is a hotspot in the field of genetics (34,35). Individual treatment based on genes will be the main trend in the future, with the interpretation of human genetic maps and advances in genetic disease research.…”
Section: Discussionmentioning
confidence: 99%